Предмет: Алгебра,
автор: odinokiy26
помогите упростить выражение
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
1.(√3+√x)(√3-√x)=3-x
2.(√x+√3)^2=x+2*√x*√3+3=x+2√(3x)+3
3.(2√3-3√2)²=(2√3)²-2*2√3*3√2+(3√2)²= =4*3-12√6+9*2=12-12√6+18=30-12√6
4.(5√3-√11)(√11+5√3)=(5√3-√11)(5√3+√11)=(5√3)²-(√11)²=25*3-11=75-11=64
4.(√(2a)+b)(2a-b√(2a)+b²)=(√(2a))³+b³=V(2a)³+b³
Похожие вопросы
Предмет: Другие предметы,
автор: grellway
Предмет: Другие предметы,
автор: Депрессионика
Предмет: Английский язык,
автор: Владислав061
Предмет: Математика,
автор: nikigta
Предмет: Английский язык,
автор: vasa49